Inhibitors of the Ras Superfamily G-proteins. - Tamanoi, Fuyuhiko (Enzymes, 2014)
Targeted toward researchers in biochemistry, molecular and cell biology, pharmacology, and cancer, this is the second part of The Enzymes' volumes that discuss inhibitors of the Ras superfamily G-proteins. Key features: Contributions from leading authorities, Informs and updates on all the latest developments in the field.